Locational Determinants of Outward Foreign Direct Investment of China's Banking Sector: Developed vs Developing Countries - An, Lian; Tao, Jiayao; Yan, Yuyang (International Journal of Business Management and Finance Research, 2025)
This paper investigates the empirical determinants of China banking sector outward foreign direct investment (OFDI) to developed and developing countries. The determinants include those drawn from extant theory on overseas investment and those deemed relevant to China’s circumstances. Adopting country-wide bank FDI data from 2000-2015, a most updated panel dataset was constructed. By relying on zero inflated model, this paper finds that the standard determinants of OFDI flows established within the western context only provides partial explanation of Chinese banking sector’s OFDI strategies and there are striking differences between developed and developing countries in their appeals to Chinese banking OFDI. Specifically speaking, the differences are: 1) Chinese OFDI to developing countries exhibit efficiency-seeking and market-seeking motives. 2) Inflation targeting regime in developed country encourages FDI while fixed exchange rate regime and monetary aggregate targeting in developing countries discourage FDI. 3) Macroeconomic environment and banking sector in developed country matter to the Chinese banking FDI, and those of developing countries do not matter. 4) Chinese banking OFDI tend to flow to developing countries with poor institutions but to developed countries with good institutions. 5) Capital openness in developing countries deter FDI and does not matter for developed countries.